Evaluation of anti-carbamylated protein antibodies as a potential biomarker in assisting the diagnosis of rheumatoid arthritis and its correlation with disease activity - Othman, Maizatul Akmal (2018)
Rheumatoid arthritis (RA) is an inflammatory rheumatic disease characterized by the presence of autoantibodies. This study aims to determine the sensitivity and specificity of anti-carbamylated protein (anti-CarP) antibodies in rheumatoid arthritis (RA) patients in relation to rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP) antibodies, C-reactive protein (CRP) as well as to determine their association with disease activity score-28 (DAS28) and health assessment questionnaire (HAQ) score. This study included 105 RA patients (48 RFpositive and 57 RF-negative patients) conducted at Hospital Universiti Sains Malaysia (HUSM) from January 2015 until February 2016. Fifty healthy controls (HCs) were included. CRP, RF, anti-CCP and anti-CarP antibodies were measured. HAQ was administered to each of the study participants. DAS28 of the 105 RA patients was measured. The level of anti-CarP antibodies was significantly increased in the RA patients compared to that in the HCs (p=0.042). The sensitivity and specificity of anti-CarP antibodies in RA patients were 42% and 78%, respectively. The presence of anti-CarP antibodies was significantly associated with RF (p=0.019) and the HAQ results (p=0.010). However, there was no significant association ofanti-CarP antibodies with anti-CCP antibodies and CRP (p=0.564 and p=0.075, respectively). Furthermore, a significant association between anti-CarP antibodies with DAS28 was not found (p=0.165). This study provides further evidence that the level of anti-CarP antibodies is significantly elevated in RA patients. In addition, this study showed that anti-CarP-positive RA patients more likely to demonstrate increased disability compared to anti-CarP-negative RA patients. Therefore, anti- CarP antibodies have a potential to be further develop as a biomarker to aid in the diagnosis and prognosis of RA.